1989
DOI: 10.1288/00005537-198909000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal leishmaniasis in brazil

Abstract: The clinical diagnosis and laboratory identification of Leishmania braziliensis braziliensis, a parasitic disease affecting the upper aerodigestive tract, is difficult. A retrospective computer-assisted analysis of patient records was done after examination of 58 patients with mucosal leishmaniasis in an endemic area of L. braziliensis braziliensis in Bahia, Brazil during January 1987. Biopsies of clinically active and clinically inactive mucosal patients were examined for parasites using routine hematoxylin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
0
30
0
2
Order By: Relevance
“…Marsden 25 suggested that even low doses of MA for the TTM of CL may prevent the occurrence of mucosal lesions in the future. Furthermore, Zajtchuk and others 26 did not observe significant differences in the development of mucosal lesions, within a period of 4.6 years, between low-dose (10 mg Sb…”
mentioning
confidence: 78%
“…Marsden 25 suggested that even low doses of MA for the TTM of CL may prevent the occurrence of mucosal lesions in the future. Furthermore, Zajtchuk and others 26 did not observe significant differences in the development of mucosal lesions, within a period of 4.6 years, between low-dose (10 mg Sb…”
mentioning
confidence: 78%
“…13,14 Few studies exist in which a complete otolaryngological examination was carried out. 15 Radiological evaluation of patients with ML has shown erosion of the nasal septum, deformity of the nasal pyramid and alterations of the nasal conchae. 16 In a previous study, we called attention to the fact that mucosal involvement, in a high percentage of cases, occurred in the form of multiple lesions, and that this influenced the clinical evolution of the disease and therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite identification is difficult and sensitivity reports vary with different techniques, from 0.2% with direct smear to 68.6% when various methods are used (Weigle et al 1987, Zajtchuk et al 1989, Schubach et al 2001, Disch et al 2005. In cases where there is a strong clinical suspicion and no parasite is isolated, treatment is prescribed with pentavalent antimony which is highly effective, but has been associated with frequent adverse effects: malaise, headache, muscle pain, joint pain and hepatic, pancreatic, renal, hematologic, and cardiac toxicity that has lead to death in some cases (Chulay et al 1985, Hepburn et al 1994, Aronson et al 1998.…”
Section: ) the Inter-observer Agreement Was Excellent For Both Testsmentioning
confidence: 99%